Fotobiomodulação com luz âmbar no tratamento do Melasma: ensaio clínico, randomizado, controlado, duplo cego - Galache, Thaís Rodrigues (2023)
Introduction: Facial Melasma (FM), the main pigmentation disorder in women (90% of cases), has a partially known etiology. Tranexamic acid (ATX) treats FM by inhibiting the conversion of plasmin to plasminogen and activating autophagy. In vitro studies indicate that amber photobiomodulation (FBM) also activates autophagy. Objective: To evaluate the effect of amber FBM on FM, compared with ATX. Material and Method: This controlled, randomized, double-blind study had patients divided into 2 groups: FBM with amber LED + placebo cosmetic (Group 1) and sham FBM + 5% tranexamic acid cosmetic (Group 2). Women aged between 35 and 50 years, phototypes II to IV and who had FM were included. Participants who were using contraceptives, IUDs, hormone replacement therapy, autoimmune diseases, photosensitive medications and recent facial treatments were excluded. Participants received treatments weekly for 12 weeks and also used the product at home during this period. All participants used sunscreen provided by the researcher throughout the study. Results: 21 women aged between 39 and 49 years were included, 10 in the FBM group and 11 in the ATX group. No significant differences were found in the intragroup analysis in the MASI parameter over time for both ATX (13.8 ±2.8; 11.7 ±2.1; 11.8 ±2.2) and FBM (16.4 ±3.0; 16.8 ±2.2; 16.2 ±2.0), as well as no significant differences were found between the groups in all periods investigated. The Global Face Assessment revealed improvements in FM in both groups, with a median score of 4 [4-5] for PBM and 4 [3-4] for TXA. No significant differences were observed between the two treatments. A score of 4 represents a slight improvement, approximately 25%, with notable evidence of remaining hyperpigmentation. In the objective assessment of pigmentation intensity, no significant differences were observed in the FBM group in the intragroup comparison over the treatment time (623,658 ± 12,397; 632,800 ± 10,397; and 642,424 ± 12,134 for PBM. On the other hand, an increase was observed in the ATX group in the intensity of pigmentation at baseline in relation to the sixth week of treatment (600,325 ± 1,820; 641,088 ± 9,914; and 635,308 ± 11,569 for TXA). In the comparison between groups, no differences were found at any of the times evaluated. An improvement in quality was observed of participants' lives, as indicated by reduction in MelaQoL questionnaire scores (47.9 ± 15.6; 37.0 ± 17.0; and 19.3 ± 11.5 for PBM; 46.6 ± 12.9; 38.1 ± 9.7; and 26.8 ± 13.6 for TXA at baseline, in the sixth week and after completion of treatment, respectively). This reduction was significant after the sixth week of treatment in both groups , although no difference in quality of life was observed between the two groups. In general, only mild and transient adverse effects were found, such as erythema, flushing. Conclusion: In this pilot study, no improvement effects were found in FM throughout the treatment and follow-up based on the MASI index in any of the treatments, nor were any differences found between treatments.